(untitled) (The Planet, 2024)
Introduction: The utilization of fine needle aspiration cytology (FNAC) in the examination of the thyroid gland has proven to be a dependable and economically efficient approach in the diagnosis of thyroid diseases. Due to the potential influence of operator proficiency on FNAC outcomes, there exists a pressing necessity to investigate the correctness of FNAC. Objective: The present study was aimed at assessing the USG Guided FNAC in thyroid nodule diagnosis. Methods and Materials: This Observational Prospective Study was performed in the department of Otolaryngology & Head Neck Surgery, Dhaka Medical College Hospital. Dhaka over 6 months duration from January 2019-June 2019. A total of 73 patients with thyroid swelling were selected after taking informed written consent and fulfilling the inclusion criteria. Smears were taken by standard procedure and then was stained with papanicolaou stain and haematoxylin and eosine stain. The smears were classified into categories like benign, indeterminate, malignant, and unsatisfactory. The sensitivity, specificity, positive and negative predictive value, and accuracy of USG Guided FNAC was calculated and compared to already available data. Appropriate statistical analysis was done to make comparison between final histopathological findings with initial USG Guided FNAC findings. Results: According to the findings of USG Guided FNAC nearly half (43.83%) of the patients had Multinodular goiter, Followed by colloid goiter (16.43%). Only 18(24.66%) Patients had carcinoma. From histopathological diagnosis, 55 patients had benign lesion and 18 patients had carcinoma. So the efficacy of USG Guided FNAC of diagnostic tool of solitary thyroid nodule where the sensitivity, specificity, PPV, NPV, PLR, NLR of USG Guided FNAC were 94.73%, 100%, 100%, 98.18%, 0 and 0.052 respectively. Conclusion: The findings of this study indicate that the USG Guided (FNAC) treatment had a specificity level of 100%, therefore suggesting its effectiveness as a minimally invasive approach. The present investigation revealed a sensitivity rate of 94.73% for ultrasound-guided fine-needle aspiration cytology (FNAC) in the United States. Therefore, it may be inferred that the diagnosis is accurate in most cases.